Analysis of aerobic and anaerobic endurance in futsal extracurricular - Sanusi, Rajib; Arifin, Ramadhan; Fauzan, Lazuardy Akbar (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
Participants in the futsal extracurricular programme at SMPN 1 Babirik often experience fatigue during competitions, which indicates a weak physical condition, particularly with regard to endurance. This study aims to analyse participants' aerobic and anaerobic endurance in order to prepare a more effective and targeted exercise programme. The research method uses a quantitative approach with descriptive methods. The study population consisted of 20 futsal extracurricular participants, sampled using the total sampling technique. The Multistage Fitness Test (MFT) was used to measure aerobic endurance and the Running-based Anaerobic Sprint Test (RAST) was used to measure anaerobic endurance. The results showed that the students' aerobic endurance was mostly in the very bad (75%), bad (20%) and sufficient (5%) categories, with an average score of 32.35. Anaerobic endurance, meanwhile, showed better results: 80% in the very good category and 20% in the good category, with an average maximum power of 223 watts, a minimum power of 124 watts and an average fatigue index of 2.55. This study indicates an imbalance between aerobic and anaerobic endurance. Therefore, a programme of exercises focused on improving aerobic endurance is needed. Further research using a wider sample size is recommended to make the results more representative.